Roundwood and biomass logistics in Finland and Sweden - Väätäinen, Kari (Array, 2020)
Logistics of roundwood and biomass comprise a high number of operations, machinery, storage sites and transportable roundwood and biomass assortments. Moreover, complex and highly varying operational environment through the year poses logistics challenges incurring additional costs. An extensive review of studies was conducted in Sweden and Finland concerning roundwood and biomass logistics, starting from roadside landings and ending with delivery to a mill or a conversion facility. The main aim of the review was to describe trends in roundwood and biomass logistics since the start of the century. Papers were classified to categories of truck transports and roads, terminals, multimodal transports, storage and supply chain logistics. Slightly over 50% of reviewed articles were constrained to biomass only, 31% to roundwood only and 14% to both. Rapid technology development, amendments concerning road transports, increasing environmental concerns and forestry sector"s push to decrease the logistics costs can be seen as the biggest drivers for the reviewed studies and their study objectives. These aspects will also drive and increase the demand for research and development in roundwood and biomass logistics in the future.